Exploring molecular pathology of chronic kidney disease in systemic sclerosis by analysis of urinary and serum proteins. Issue 1 (7th January 2021) - Stern, Edward P; Unwin, Robert; Burns, Aine; Ong, Voon H; Denton, Christopher P
Abstract: Objective: Renal involvement is common in systemic sclerosis (scleroderma; SSc) and includes chronic kidney disease (CKD). We have performed analysis of urinary proteins to gain insight into local molecular pathology of CKD in SSc and identify candidate markers for use in clinical trials. Methods: To evaluate urinary proteins that might specifically reflect SSc-related CKD, patients were recruited with confirmed SSc and stratified for the presence or absence of CKD. Controls included patients with CKD and no SSc, in addition to healthy volunteers. Candidate markers were measured in serum and urine by multiplex immunoassay testing for IL6, IL18, TNF-α, monocyte chemoattractant protein 1 (MCP1), monocyte chemoattractant protein 3 (MCP3), VEGF and the soluble adhesion molecules vascular cell adhesion molecule 1 (VCAM-1) and intercellular adhesion molecule 1 (ICAM-1). Results: One hundred and two subjects were examined, including patients with SSc with no evidence of CKD ( n = 40), SSc with CKD ( n = 39), non-SSc CKD ( n = 11) and healthy volunteers ( n = 12). Urinary levels of IL6, MCP1, TNF-α, MCP3, IL18 and ICAM-1 were elevated in SSc patients compared with healthy controls. The most significant differences were for MCP1 and ICAM-1 (both P < 0.0001), and these analytes also showed the most significant differences between groups overall ( P = 0.003 for MCP1 and P < 0.0001 for ICAM-1). These markers showed a trend (MCP1, P = 0.0868) or a significant difference (ICAM-1, P = 0.0134) between SSc–CKD and SSc with normal renal function. Conclusion: Urinary levels of candidate molecular markers appear to reflect SSc–CKD more than serum markers. MCP1 and ICAM-1 are promising molecular markers for SSc–CKD and might be potential biomarkers of SSc renal involvement. This might be explored in future prospective analyses.